Feasibility, acceptability and effectiveness of a culturally informed intervention to decrease stress and promote well-being in reservation-based Native American Head Start teachers - Deborah H. Wilson; Danielle German; Adrian Ricker; Hilary Gourneau; Ginger C. Hanson; Justin Mayhew; Teresa N. Brockie; Michelle Sarche (BMC, 2023)
Abstract Background While benefiting from strong cultural ties to family, land and culture Native Americans residing on reservations experience psychological distress at rates 2.5 times that of the general population. Treatment utilization for psychological health in reservation-based communities is low with access to culturally appropriate care lacking. Evidence suggests that for mental health treatment, Native Americans prefer culturally informed care that respects Native perspectives on health and well-being. Methods To decrease stress and promote well-being in tribal Head Start teachers we adapted and implemented a culturally focused intervention within a community-based participatory research framework using mixed methods. Feasibility and acceptability of the adapted 5-session curriculum was tested in a single arm intervention study with a sample of 18 teachers on the Fort Peck Reservation. Participants completed surveys at baseline and upon completion of the intervention. Within session observations and two post-intervention focus groups (n = 8, n = 10) were conducted to elaborate and explain the quantitative results eliciting participant experience of intervention effectiveness and feasibility, acceptably and appropriateness. Implementation outcomes were assessed quantitatively using the Acceptability of Intervention, Intervention Appropriateness, and Feasibility of Intervention measures. Results Quantitively, attendance rate overall was 93% with no dropouts. Pretest/posttest surveys were analyzed using t-tests and Hedges g to measure effect size. Contrary to our hypothesis, self-perceived stress showed a small positive effect size, indicating that participants were more stressed post intervention. However, depression decreased, with tribal identity and resilience showing positive effect sizes. Content analysis for the qualitative data collected within session observations and post intervention focus groups revealed how lifetime traumas were affecting participants, providing some explanation for the increase in stress. Teachers reported that the sessions helped their psychological health and well-being, supporting feasibility of future interventions. Acceptability scored highest with a mean (SD) of 4.25 (.84) out of 5, appropriateness 4.18 (.86) and feasibility 4.06 (.96) supporting intervention to be acceptable, appropriate, and feasible. Conclusion Utilizing a culturally based intervention to buffer stress and support the well-being of reservation-based teachers showed promise in helping them recognize their cultural strengths, stress, and need for ongoing support. Implementation outcomes show that intervention scale-out is feasible.